2005
DOI: 10.1175/jas3457.1
|View full text |Cite
|
Sign up to set email alerts
|

A Refinement of the Millionshchikov Quasi-Normality Hypothesis for Convective Boundary Layer Turbulence

Abstract: The Millionshchikov hypothesis of quasi-normal distribution of fourth-order moments fails for convective conditions where the probability density functions of temperature and vertical velocity fluctuations are skewed. This is shown for aircraft and large-eddy simulation (LES) data, and new closures for fourth-order moments that take the skewness into account are suggested. These new closures are in very good agreement with the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(89 citation statements)
references
References 13 publications
3
86
0
Order By: Relevance
“…A quasi-normal FOM even when TOM is non-zero, agrees with the hypothesis of Millionshchikov (1941) which forms the basis for a large number of closure models (see Gryanik et al, 2005, for an overview). However, some recent theoretical studies, measurement data, and LES data suggest that this hypothesis would not be valid for temperature in the CBL (also see Gryanik et al, 2005, for an overview).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A quasi-normal FOM even when TOM is non-zero, agrees with the hypothesis of Millionshchikov (1941) which forms the basis for a large number of closure models (see Gryanik et al, 2005, for an overview). However, some recent theoretical studies, measurement data, and LES data suggest that this hypothesis would not be valid for temperature in the CBL (also see Gryanik et al, 2005, for an overview).…”
Section: Discussionsupporting
confidence: 82%
“…However, some recent theoretical studies, measurement data, and LES data suggest that this hypothesis would not be valid for temperature in the CBL (also see Gryanik et al, 2005, for an overview). Gryanik and Hartmann (2002) suggested furthermore a parameterization between the FOM, skewness, and variance of turbulent temperature fluctuations which can be tested as soon as a larger number of measurement cases on turbulent temperature fluctuations with rotational Raman lidar have become available.…”
Section: Discussionmentioning
confidence: 99%
“…Our model indicates a different origin for the strong localized events, associated with a positive feedback in the vertical between nonlinear steepening and wave motions, and is consistent with the simulations that indicate that a more stably stratified flow has stronger bursts in a plage of parameters. This study may thus lead to more useful parametrizations of stably stratified flows in weather and climate models, by formulating a stochastic eddy-noise [27] which explicitly incorporates the non-linear coupling described herein (for a quasi-normal closure, see [28]). …”
mentioning
confidence: 99%
“…For this case a number of analytical relations exists between higher order moments. As they were found to scale very well with Reynolds averages, GH2002 and Gryanik et al (2005) suggested to replace the quasi-normal (QN) model with a new set of closures (see Kupka & Robinson 2007 for a discussion).…”
Section: Models For Third and Fourth Order Momentsmentioning
confidence: 99%